Contribution of the Tourism Sector and Economic Growth in Banyuwangi Regency - Kushariyadi, Kushariyadi; Prayitno, Hadi; Salma, Nur; Sitanggang, Juwita Magdalena (International Journal of Economics (IJEC), 2025)
The purpose of this research is to determine the Contribution of the Tourism Sector to Economic Growth in Banyuwangi Regency. The method used in this research is qualitative research with field research type. Field research is one way to collect data directly from the location or object of research. This type of research is generally conducted by observing, interviewing, or measuring and sampling. The location of this research is in Banyuwangi Regency, specifically in the tourist attractions of Pulau Merah Beach and Teluk Hijau. As for the interviewees, they are employees of the Tourism Office and residents around the tourist attractions. The results of this study indicate that the tourism sector is an economic sector that has great potential in contributing to the economic growth of a country and region. Tourism can create jobs, increase foreign exchange earnings, and strengthen local economic growth. Based on the research findings, it can be concluded that the development of tourism in Banyuwangi Regency contributes to the local economy and community directly.